THE THE SYBOLIC MEANING OF THE DANCE MOVEMENT OF BEDHAYA AMBADYA TIRTA BY ANUGRAH NATALIN NILAWATI THE SYMBOLIC MEANING OF THE DANCE MOVEMENT OF BEDHAYA AMBADYA TIRTA BY ANUGRAH NATALIN NILAWATI - Fatmasari, Indah Putri (Solah, 2025)
Abstract: This study aims to describe the movements of the Bedhaya Ambadya Tirta dance created by Anugrah Natalin Nilawati and explain the symbolic meanings contained within it. The focus of this study is on the structure of the movements and the cultural and spiritual messages conveyed through the dance. The method used in this study is a qualitative method with a descriptive approach. Data collection techniques were carried out through interviews with dancers and music arrangers, direct observation of dance performances, as well as relevant visual and written documentation. The results of the study show that the Bedhaya Ambadya Tirta dance has highly structured, gentle, and meaningful movements. These movements represent elegance, harmony, and the connection between humans and nature and the spiritual dimension. Each movement not only reflects aesthetics and traditional values but also serves as a medium for conveying profound messages about purity, peace, and inner balance. The symbolism embedded in this dance depicts the process of uniting the human soul with the universe, making it not only a form of artistic expression but also a means of spiritual contemplation and cultural preservation. Symbolic Meaning of the Movements in the Bedhaya Ambadya Tirta Dance by Anugrah Natalin Nilawati